1987
DOI: 10.1111/j.1476-5381.1987.tb11206.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in acetylcholine concentrations in the brain of ‘old’ rats following treatment with pyrithioxin (Encephabol)

Abstract: Treatment of old rats, for two to three weeks, with pyrithioxin led to an increase in the levels of endogenous acetylcholine (ACh) in the cortex and the striatum but not in the hippocampus. Pretreatment of old rats with pyrithioxin also increased the resting release and the K+‐stimulated release of radioactive ACh from brain slices in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
3
15
0
1
Order By: Relevance
“…The effect of pyrithioxin on acetylcholine levels in old and young rats is illustrated in Table 1. The effect in the old rats essentially replicated those found by Martin and Vyas (1987) although the levels of acetylcholine were less than those found in their experiment. Unlike the findings of Martin and Vyas (1987) the drug increased acetylcholine content irrespectively of brain region.…”
Section: Neurochemical Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The effect of pyrithioxin on acetylcholine levels in old and young rats is illustrated in Table 1. The effect in the old rats essentially replicated those found by Martin and Vyas (1987) although the levels of acetylcholine were less than those found in their experiment. Unlike the findings of Martin and Vyas (1987) the drug increased acetylcholine content irrespectively of brain region.…”
Section: Neurochemical Resultssupporting
confidence: 75%
“…Martin and Vyas (1987) showed that the drug enhances both acetylcholine concentrations and acetylcholine release in old rats, a combination of effects that differs from that generally found for cholinergic drugs which enhance release (Tucek, 1984), and which may be specific to aged animals with reduced acetylcholine stores. In support of the possibility that the present improvement seen in spatial retention in old rats is associated with a facilitation of cholinergic activity, a previous study has shown that 3,4-diaminopyridine, which stimulates acetylcholine release improves radial maze performance in aged rats (Davis, Idowu and Gibson, 1983).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has recently been reported (Martin and Vyas, 1987) that the treatment of old rats with pyritinol produces an increase in cortical ACh levels. Both the resting and the K+-stimulated release of ACh from slices is facilitated when this is measured ex vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These various drugs have demonstrated differing effects on brain acetylcholine levels, acetylcholine release (basal, induced), high affinity choline uptake activity, cGMP levels, muscarinic receptor functionality, etc. However, their cellular and the subcellular targets in the cholinergic system and in the cognitive process have not been well defined up to now (Greiner et al, 1988;Martin and Vyas, 1987;Martin and Widdowson, 1990;Pepeu and Spignoli, 1989;Pilch and M/,iller, 1988;Seyfried, 1989;Shih and Pugsley, 1985). Although pharmacological effects on other non cholinergic systems (monoaminergic, aminoacidergic, peptidergic) have been rejected (Greiner et al, 1988) or considered to be minimal (Pepeu and Spignoli, 1989), other trophic or regulatory effects have been postulated in relation to corticosteroids and other factors (Mondadori and Petshke, 1987) and to phospholipid/cholinergic system interactions (Martin and Widdowson, 1988;Gelbmann and Miiller, 1991).…”
Section: Introductionmentioning
confidence: 99%